Utilizing YouTube Videos as Instructional Media to Advance EFL Learners’ Speaking Fluency (Evidence from Indonesian Native Speakers as EFL Learners) - Pakpahan, Marnangkok (Medan Resource Center, 2024)
This study investigated the impact of using YouTube videos as instructional media on advancing speaking fluency in an English conversation class. A quasi-experimental design with pre- and post-tests was employed, involving 30 first-semester students from an English Language and Culture program in Pontianak, Indonesia, using total population sampling. Data collection included two oral speaking tests, a speaking fluency rating scale, and a questionnaire. A mixed-methods approach (quantitative and qualitative) was used for data analysis. Results showed that the mean post-test score (78) was significantly higher than the pre-test score (67.65), with a difference of 10.35 points. This indicates that YouTube videos are highly effective in improving EFL learners’ speaking fluency. The study highlights the importance of incorporating effective instructional media in EFL education to better address students' learning needs and enhance engagement, ultimately leading to more effective language learning outcomes.